Sequential measurements of IGF-I serum concentrations in adolescents with Laron syndrome treated with recombinant human IGF-I (rhIGF-I) - Breil, Thomas; Kneppo, Carolin; Bettendorf, Markus; Müller, Hermann L.; Kapelari, Klaus; Schnabel, Dirk; Woelfle, Joachim (The journal of pediatric endocrinology and metabolism, 2018)
Background: Recombinant human insulin-like growth factor 1 (rhIGF-I) has been approved as an orphan drug for the treatment of growth failure in children and adolescents with severe primary IGF-I deficiency (SPIGFD) with little pharmacokinetic data available. Therefore, sequential measurements of serum IGF-I, glucose, potassium, insulin and cortisol were performed in patients treated with rhIGF-I to evaluate their significance in safety and efficacy. Methods: Repetitive blood samples were taken after meals before and 30, 60, 120, 180 and 360 min after rhIGF-I injections in two male patients with Laron syndrome at times of dose adjustments. Results: Maximal IGF-I concentrations were observed 2 h after injections (495 ng/mL) and concentrations were still higher 6 h after injections than at baseline (303 ng/mL vs. 137 ng/mL). Thirteen percent of all and 33% of maximum IGF-I concentrations were greater than +2 standard deviation score (SDS) calculated for bone age (BA) (IGF-I SDS BA) rather than chronological age (CA) as BA was significantly delayed to CA by 3.2 years (p=0.0007). Height velocities correlated with individual maximum IGF-I SDS BA (ρ=0.735; p<0.0001). Serum insulin, cortisol and glucose did not correlate with IGF-I concentrations, but serum potassium showed a negative correlation (ρ=−0.364; p<0.0001) with IGF-I concentrations. Conclusions: Sequential measurements of serum IGF-I, glucose and potassium in patients with Laron syndrome may aid in optimizing and individualizing rhIGF-I treatment. IGF-I concentrations should be referenced according to BA which better reflects the biological age. The inverse correlation of IGF-I and serum potassium concentrations after injections of rhIGF-I has not been reported before and warrants further consideration.
Gesehen am 15.08.2019